Lead in modern and contemporary art - Hecker, Sharon; Bottinelli, Silvia (London, UK ; New York, NY : Bloomsbury Visual Arts, 2021)
"Lead in Modern and Contemporary Art is the first edited volume to critically examine uses of lead as both material and cultural signifier in modern and contemporary art. The book analyzes the work of a diverse group of artists working in Europe, the Middle East, and North America, and takes into account the ways in which gender, race, and class can affect the cultural perception of lead. A distinguished group of international contributors from various fields, both established and early in their careers, explore lead's relevance from a number of perspectives, including art history, technical art history, art criticism and curatorial studies. Drawing on current art historical concerns with materiality, this volume builds on recent exhibitions and scholarship that reconsider the role of materials in shaping artistic meaning, thus giving a central relevance to the object and its physicality"--
List of FiguresList of ContributorsAcknowledgements Introduction: To Be Continued ... Silvia Bottinelli (Tufts University, USA) and Sharon Hecker (independent scholar)1. A Most Insidious Poison Taking Advantage of our Necessities: A Brief Historical Introduction to Lead and Lead Poisoning, Christian Warren (Brooklyn College -- The City University of New York, USA)2. Lead's Historic Transformations, Spike Bucklow (University of Cambridge, UK)3. In the Backyard at Burcroft: Henry Moore's Experiments in Lead, Rowan Bailey (University of Huddersfield, UK)4. The Weakness of Lead: Materiality and Modern American Sculpture, Marin R. Sullivan (Harry Bertoia Foundation & Cheekwood Estate and Gardens, USA)5. Due Process: Richard Serra's Early Splash/Cast Works, Jeffrey Weiss (The Institute of Fine Arts, USA)6. Exorbitant Matter: Materiality According to Lynda Benglis, Luke Naessens (Princeton University, USA)7. Lead in the Lexicon of Gilberto Zorio's Sculpture, Elizabeth Mangini (California College of the Arts, USA)8. The Stopping Power of Lead: Luciano Fabro, Giuseppe Penone, and Marisa Merz, Sharon Hecker (independent scholar)9. 'Mankind needs some lead so as to be somewhat heavier': Beuys, Alchemy, and Duchamp, Claudia Mesch (Arizona State University, USA)10. A Conversation with Remo Salvadori, Sharon Hecker (independent scholar) and Silvia Bottinellii (Tufts University, USA) Critical Introduction by Rosalind McKever (Victoria and Albert Museum, UK)11. Two Views of Anselm Kiefer: In the Studio and In the Museum Kiefer Speaks About Lead with Karl Ove KnausgaardLoaded Lead: Anselm Kiefer in the Collection of the Israel Museum, Sharon Tager and Adina Kamien (The Israel Museum, Jerusalem)12. Anthony Caro: Lead and Wood Sculptures. 1980-1989, Karen Wilkin (independent scholar)13. The New British Sculpture and the Poetics and Pragmatics of Lead, Jon Wood (independent scholar)14. Organizing Against an Invisible Threat. Lead According to Futurefarmers and Mel Chin, Silvia Bottinelli (Tufts University, USA) 15. An Interview with Daniela Rivera: The weight of lead and painting beyond the surface, Silvia Bottinelli (Tufts University, USA) and Sharon Hecker (independent scholar)BibliographyIndex.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 07, 2022).
eBooks on EBSCOhost
Keywords: Lead in art; Artists' materials -- Case studies; Plomb dans l'art.; Matériel d'artistes -- Études de cas; Artists' materials; Lead in art; Case studies